PENGARUH STRUKTUR KEPEMILIKAN, RETURN ON ASSET DAN LEVERAGE TERHADAP MANAJEMEN LABA - Yuliana Gunarti (Universitas Slamet Riyadi, 2015)
This research purposed to analyze the effect of managerial ownership, institutional ownership, return on asset and leverage on earnings management. Sampling was purposive sampling method, in order to obtain a sample of 32 manufactured companies consumer goods industry listed on The Indonesia Stock Exchange in the year of 2011 - 2013. This research used library research methods and documentation. Data was taken from the Indonesia Capital Market Directory (ICMD) and Financial Statements manufactured company consumer goods industry. The analysis method of this research that used was multiple regressions. The result showed that board of managerial ownership, institutional ownership, return on asset and leverage simultaneously influence the earnings management. Partial examination showed that board of (1) managerial ownership has significant negatively influence the earnings management, (2) institutional ownership has significant negatively influence the earnings management, (3)return on asset has positive but it has not significant influence on earning management and (4) leverage has negative but it has not significant influence on earning management. Keywords: Ownership Structure, Return on Asset, Leverage, Earning Management.